Perceptions of sustainability in heritage studies - Albert, Marie-Theres 1948- (Heritage studies, 2015)
"This publication is the fourth in the Heritage Studies series and aims to reflect upon the many dimensions of sustainability and sustainable development within the Heritage Studies discourse. Sustainability as a concept and sustainable development as a goal are presented in official policies within UNESCO's understanding of heritage, in its paradigmatic reflections and in the diversity of theories and methods, including many different and sometimes conflicting understandings of sustainability within this discourse. Thus, the contributors to this publication discuss sustainability as it directly concerns the potential of different approaches to World Heritage and Intangible Heritage. The inclusion of the four dimensions of sustainability...environmental, economic, social and cultural...into the Heritage Studies discourse opens a new perspective on the discourse itself"...Provided by publisher